Emerging Lead Free Ferroelectric Materials-Potassium Bismuth Titanate & Sodium Bismuth Titanate - Pahuja, Poonam; Jitender, (Innovations in Science and Technology: Shaping a Sustainable Future (Vol. 2), 2024)
With the advancement in technology, the environment and health are two most affected areas that need to be considered. Among all piezoelectric ceramics, Lead Zirconate Titanate is most widely used in almost all devices such as actuators, transducers, sensors, memory devices, switches, oscillators, etc. Lead being toxic should be replaced by some eco-friendly substitute. Bismuth Potassium Titanate (KBT) and Sodium Bismuth Titanate (NBT) are two emerging materials that can substitute PZT. Scientists are working on different methods of preparation, trying different dopants and substitutes in KBT and NBT to achieve the nearly same properties as PZT as high dielectric constant, large piezoelectric coefficient, high density, high breakdown strength, etc. Li, K, La, Sm, Dy, Ho, Nb, Mn, Fe, and Sb are some of the major dopants in NBT and KBT, which are recently been explored. Substitution of rare earth elements La, Sm, Ho and Dy in NBT resulted in an increase in grain size proportional to the radius of rare earth dopant. Further these ions also increase its temperature range for actuator applications. Particularly, Sm doping in NBT gives ultra-high storage density and efficiency. Li+ and K+ substitution in NBT increases its conductivity. Solid Solutions of barium titanate, strontium titanate and their derivatives with KBT & NBT exhibit unique properties. This chapter provides a brief outlook on the latest research on these two materials.